Metabolic syndrome is inversely related to soluble receptor for advanced glycation end products: a study in mother-infant pairs - Klenovicsova, K.; Boor, P.; Hrachova, J.; Furkova, K.; Sebekova, K. (Вiopolymers and Cell, 2011)
Aim. In the elderly subjects metabolic syndrome (MetS) seems to be associated with low levels of circulating
protective soluble receptor for advanced glycation end products (sRAGE). This secondary study aimed to
answer whether this phenomenon is manifested from early childhood. Methods. 73 mothers and their 77
infants (4-to-12-months of age) were included in the study. Mothers were classified according to the
presence of MetS components as negative (n = 32), those with pre-MetS (insulin resistance + 1 sign of MetS,
n = 27) and overt MetS (n = 14). sRAGE and carboxymethyllysine (CML) were determined in the mothers
and the infants. Results. Mothers with pre- and overt MetS displayed lower sRAGE levels, while in their
children only a trend towards decline was observed. sRAGE levels significantly and inversely correlated
with insulin sensitivity and BMI/body weight. No difference in CML levels across the groups was observed.
Conclusions. Metabolic syndrome is associated with decreased levels of sRAGE in the mothers and a
tendency towards decline of sRAGE in their offspring. Infants of mothers with MetS maintain normoglycemia on the account of higher insulin levels.
Keywords: metabolic syndrome, mother-child pairs, QUICKI, sRAGE, insulin resistance, CML. Мета. У пацієнтів похилого віку розвиток метаболічного синдрому (МетС) асоційований з низьким рівнем циркулюючого
розчинного рецептора для кінцевих продуктів повного глікозилювання (sRAGE). Мета цієї роботи полягала у пошуку відповіді на питання, чи проявляється таке явище у ранньому дитинстві? Методи. Досліджено 73 матері і 77 дітей віком від
чотирьох до 12 місяців. Залежно від присутності компонентів
МетС матерів розділили на три групи: негативна (n = 32) – без
компонентів МетС; з початковою стадією МетС (резистентність до інсуліну + одна ознака МетС, n = 27) та з явно вираженим МетС (n = 14). У матерів і дітей визначали рівень концентрації sRAGE і карбоксиметиллізину (КМЛ). Результати.
У матерів з початковою та явно вираженою стадіями МетС
встановлено нижчий рівень sRAGE порівняно з їхніми дітьми, у
яких спостерігали лише тенденцію до його падіння. Кількість
sRAGE корелює з чутливістю до інсуліну та показником BM
(індекс маси тіла) I /маса тіла. Різниці в концентрації КМЛ по
групах не знайдено. Висновки. Метаболічний синдром пов'язаний із зниженням рівня sRAGE у матерів. Показано тенденцию
до зменшення кількості sRAGE у їхніх дітей. Нормоглікемія у
дітей, у матерів яких визначено МетС, підтримується вищим
рівнем інсуліну.
Ключові слова: метаболічний синдром, пара мати–дитина,
QUICKI, sRAGE, резистентність до інсуліну, карбоксиметиллізин. Цель. У пациентов пожилого возраста развитие метаболического синдрома (МетС) ассоциировано с низким уровнем
циркулирующего растворимого рецептора для конечных продуктов полного гликозилирования (sRAGE). Цель этой работы
состояла в поиске ответа на вопрос, проявляется ли данное явление в раннем детстве? Методы. Исследованы 73 матери и
77 детей в возрасте от четырех до 12 месяцев. В зависимости
от присутствия компонентов МетС матерей разделили на
три группы: отрицательная (n = 32) – без компонентов
МетС; с начальной стадией МетС (резистентность к инсулину + один признак МетС, n = 27) и с явно выраженным МетС
(n = 14). У матерей и детей определяли уровень концентрации
sRAGE и карбоксиметиллизина (КМЛ). Результаты. У матерей с начальной и явно выраженной стадиями МетС выявлен
более низкий уровень sRAGE, в то время как у их детей наблюдалась лишь тенденция к его снижению. Количество sRAGEкоррелирует с чувствительностью к инсулину и показателем
BM (индекс массы тела) I/масса тела. Разницы в концентрации КМЛ по группам не установлено. Выводы. Метаболический синдром связан со снижением уровня sRAGE у матерей.
Показана тенденция к уменьшению количества sRAGE у их детей. Нормогликемия у детей, у матерей которых обнаружен МетС, поддерживается более высоким уровнем инсулина.
Ключевые слова: метаболический синдром, пара мать–ребенок, QUICKI, sRAGE, резистентность к инсулину, карбоксиметиллизин.